Pelatihan Kelompok Wanita Tani Aren dalam Mengolah Air Nira Menjadi Gula Semut Guna Peningkatan Ekonomi Masyarakat Desa Lamondape - Helviani Helviani; Nursalam Nursalam; Fitrah Adelina; Aan Wilhan Juliatmaja; Asni Asni; Rosmini Rosmini; Aminah Sagista (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Palm trees have high economic value because almost all their parts can be used. The problem faced by the Palm Oil Farming Women's Group in Lamondape Village is that moulded palm sugar products have low selling prices, this is because the community is not aware of innovations in diversifying palm juice products. Limited trained resources result in a lack of honed skills or abilities that can produce innovative creativity. The activity aims to process palm juice with partners into ant sugar products with a higher selling value than moulded palm sugar, with better and more attractive packaging. And carry out outreach and training activities to the community to hone innovative creative skills. The result of this activity is that the group produces ant sugar products that have higher economic value so that it can increase the income of the women's palm farming group. The women's palm farming group will be more sensitive to the potential of local resources in Lamondape Village, Kolaka Regency.